Investigation of a new implant surface modification using phosphorylated pullulan - Nagamoto, Kanako; Nakanishi, Ko; Akasaka, Tsukasa; Abe, Shigeaki; Yoshihara, Kumiko; Nakamura, Mariko; Hayashi, Hiroshi; Takemoto, Shinji; Tamura, Masato; Kitagawa, Yoshimasa; Van Meerbeek, Bart; Yoshida, Yasuhiro (Frontiers in Bioengineering and Biotechnology, 2024)
Various implant surface treatment methods have been developed to achieve good osseointegration in implant treatment. However, some cases remain impossible to treat with implants because osseointegration is not obtained after implantation, and the implants fail. Thus, this study focused on phosphorylated pullulan because of its adhesiveness to titanium (Ti) and bone, high biocompatibility, and early replacement with bone. In this study, the response of bone-related cells to phosphorylated pullulan was evaluated to develop a new surface treatment method. Saos-2 (human osteosarcoma-derived osteoblast-like cells), MC3T3-E1 (mouse calvaria-derived osteoblast-like cells), and RAW264.7 (mouse macrophage-like cells) were used. In evaluating cellular responses, phosphorylated pullulan was added to the culture medium, and cell proliferation and calcification induction tests were performed. The proliferation and calcification of cells on the surface of Ti disks coated with phosphorylated pullulan were also evaluated. In addition, bone morphogenetic protein-2 (BMP-2), an osteogenic factor, was used to evaluate the role of phosphorylated pullulan as a drug carrier in inducing calcification on Ti disks. Phosphorylated pullulan tended to promote the proliferation of osteoblast-like cells and the formation of calcification on Ti disks coated with phosphorylated pullulan. Ti disks coated with phosphorylated pullulan loaded with BMP-2 enhanced calcification. Phosphorylated pullulan inhibited osteoclastlike cell formation. These results are due to the properties of phosphorylated pullulan, such as adhesiveness to titanium and drug-loading function. Therefore, phosphorylated pullulan is effective in promoting bone regeneration when coated on titanium implants and is useful for developing a new surface treatment method.